1974
DOI: 10.1111/j.1432-1033.1974.tb03442.x
|View full text |Cite
|
Sign up to set email alerts
|

Purification and Properties of Ovalbumin Messenger RNA

Abstract: Ovalbumin messenger RNA was purified 67-fold from hen oviduct polysomal RNA by sucrose gradient centrifugation and oligo(dT)-cellulose hybridization. Ovalbumin messenger RNA activity was coincident with the main peak of absorbance after acrylamide gel electrophoresis of the purified RNA. Each purified messenger was translated over 20 times in a rabbit reticulocyte lysate, protein-synthesizing system. An apparent molecular weight of approximately 875 000 was obtained by electrophoresis under both native and den… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

2
39
0
1

Year Published

1974
1974
1981
1981

Publication Types

Select...
7
3

Relationship

0
10

Authors

Journals

citations
Cited by 96 publications
(42 citation statements)
references
References 52 publications
2
39
0
1
Order By: Relevance
“…The apparent molecular weight of the estrogen-induced RNA obtained by gel electrophoresis under non-denaturating conditions (2.0 x lo6) is considerably higher than that determined by sedimentation on dodecylsulphate-sucrose gradients (1.5 x lo6). This feature was already observed for other poly(A)-containing RNA's such as myosin-mRNA [23] and ovalbumin mRNA [24]. Since all these separations are very dependent on the secondary structure of the RNA, the molecular weights determined by reference to rRNA are misleading.…”
Section: Discussionmentioning
confidence: 92%
“…The apparent molecular weight of the estrogen-induced RNA obtained by gel electrophoresis under non-denaturating conditions (2.0 x lo6) is considerably higher than that determined by sedimentation on dodecylsulphate-sucrose gradients (1.5 x lo6). This feature was already observed for other poly(A)-containing RNA's such as myosin-mRNA [23] and ovalbumin mRNA [24]. Since all these separations are very dependent on the secondary structure of the RNA, the molecular weights determined by reference to rRNA are misleading.…”
Section: Discussionmentioning
confidence: 92%
“…Fractions (0.5-1 ml) were collected from the bottom of the tube. Palmiter (12) demonstrated that the 650 heat treatment method disaggregated OVmRNA without reducing its ability to direct OV synthesis in a reticulocyte lysate. Other workers (13,14) have also found similar heat treatments to effectively disaggregate RNA without causing thermal degradation.…”
Section: Methodsmentioning
confidence: 99%
“…Immediately after the last extraction with chloroform the aqueous phase, containing the RNA, was heated to 600 for 3 min to denature the RNA. This material was then applied directly to linear gradients of 5-20% sucrose in 0.01 M N-2-hydroxyethylpiperazine-N'-2-ethanesulfonic acid (Hepes), pH 7.5, containing EDTA (0.001 M), as described by Palmiter (15). The gradients were centrifuged at 40 at 67,000 X g., for 16 hr in a SW 27 rotor in a Beckman L-5 65 centrifuge, after which they were fractionated as described above.…”
mentioning
confidence: 99%